THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL PRODUCTIVITY IN HYBRID WORK ENVIRONMENTS - Juliandi Saputra; Oktavianti; Rizki Eka Putra (RADJA PUBLIKA, 2025)
The rapid global shift to hybrid work models has necessitated a re-examination of the well-established link between employee engagement and organizational productivity. This study investigated this relationship through a mixed-methods approach, combining a quantitative survey of knowledge workers with qualitative interviews. The results confirmed a strong positive correlation (r=.65) between engagement and productivity, with dedication being the strongest predictor. However, a critical paradox emerged: office-centric employees reported the highest engagement, while fully remote employees reported the highest productivity. Flexibly remote employees (1-2 office days) constituted a vulnerable